Pulmonary rehabilitation for patients receiving lung cancer radiotherapy: a scoping review - Chen Yao; Wang Chunyu; Jiayi Du; Yan Sisi; Kuang Yajuan; Song Suting; Hu Qu; Lei Xuejiao; Zhaoli Zhang (BMJ Open)
Objective Radiotherapy (RT) can cause a range of negative impacts in addition to the intended treatment impacts. Pulmonary rehabilitation (PR) may improve the physical and psychological conditions of patients with lung cancer receiving RT, but specific evidence is lacking. This review mapped the evidence on PR in patients with lung cancer receiving RT for intervention characteristics and outcome assessments.Data sources PubMed, EMBASE, CINAHL, Proquest, Web of Science, CNKI and WanFang were searched for studies from January 2003 to April 2025.Eligibility criteria We included randomised controlled trials and non-randomised comparative intervention studies that included centre-based PR in patients ≥18 years with lung cancer who were receiving RT. PR was defined as any type of exercise, respiratory training, or both and/or at least one additional component (eg, psychological support). Studies were excluded if they were not available in English, were not full-text articles or were non-peer-reviewed.Data extraction and synthesis Two reviewers independently screened titles, abstracts and full texts for inclusion and extracted data. PR components and the typology of outcome assessments used were mapped at the final data synthesis level.Results Out of 3120 records, nine studies were investigated in the final data synthesis. In these studies, in addition to exercise or respiratory training, psychological support and disease education were the most common components of PR. Pulmonary function, quality of life, symptom assessment and exercise performance were commonly assessed outcomes in these included studies. Although the effectiveness of PR is difficult to synthesise, the evidence for improvements in exercise performance and symptoms of dyspnoea and anxiety/depression is promising.Conclusions Evidence on PR in patients with lung cancer receiving RT is sparse, and there is a heterogeneous understanding of PR. The development of standardised PR protocols and investigation of the capabilities of PR in this growing and under-represented patient population are essential.